The Limits of Rationalist Explanations for the Development of International Security Institutions - Drgas, Michał (The Copernicus Journal of Political Studies, 2018)
In this article I argue that rationalist explanations which aspire to demonstrate why international security institutions develop, do not qualify as fully satisfactory arguments. Their limits become apparent particularly if one attempts to account on their basis for the diversity of types of institutions such as balance of power, collective security, hegemony, etc. The initial step in my analysis was to address the limitations of the three arguments which I referred to as materialist, functionalist, and evolutionist that individually make up either whole rationalist conceptions on the development of international security institutions or parts of them. Having done so, I also examined the possibilities to combine these arguments to explore whether the effort yields any extra explanatory power. The main reasons for why these explanations and their combinations fail to convincingly account for the diversity of international security institutions are threefold. First, the functionalist, evolutionist, and the functionalist-evolutionist arguments do not attempt to address the issue directly and provide only a general assertion on the factors influencing the formation of institutions instead of tackling the problem with respect to their particular types. Second, the materialist argument advances a logic of state action that justifies the creation of certain types of institutions and, at the same time, rules out the development of others. Third, it proves also incompatible with the other two arguments. The implication of this is that states would have to choose between mutually exclusive logics of action and, thus, behave in a way for which none of the arguments provides any explanation. Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14760